Religious ethical values and earnings quality : some evidence from Malaysia : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Accountancy at Massey University, Albany, New Zealand - Abdul Rahman, Rahayu (Massey University, 2012)
The main purpose of this thesis is to examine the association between religious ethical values and earnings quality. This study builds upon the principals and ethical framework of Islamic teachings (Shariah). It analyses how such ethical values affect the earnings quality of Malaysian listed firms. Shariah is the Islamic code for day-to-day conduct of individuals under Islam. It provides principles of good practices including accountability at both individual and organizational levels. It promotes justice and welfare in society by encouraging better ethical conduct. Based on these premises, it is hypothesised in this thesis that Shariah is associated with high quality reported earnings. Two different attributes of earnings quality are used to test the above hypothesis. These are earnings management and accounting conservatism. A sample of 1,878 firm-year observations from 2000 to 2007 of Malaysian firms is used for examining the association between Shariah and earnings quality. The study finds a significant negative association between Shariah, and real and accrual-based earnings management. In particular, this study finds that Shariah is associated with lower abnormal discretionary accruals, abnormal cash flow from operations, and abnormal discretionary expenses. Further, results of the study reveal that Shariah is associated with higher levels of accounting conservatism. Overall, the results suggest that Shariah is an important monitoring mechanism in limiting managerial opportunism and, consequently, enhances the quality of accounting earnings.
Keywords: Business enterprises; Islamic ethics; Business ethics; Ethics; Malaysia; Religious ethics